Peningkatan Hasil Belajar Siswa Melalui Pendekatan Saintifik Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas V di MI Guppi Borongbuah Desa Rannaloe Kecamatan Bungaya Kabupaten Gowa - Idafitriana Idafitriana; Idawati Idawati; Ainun Jariah (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The type of research used is participant PTK, where research is directly involved in the research process from the beginning until the research results are in the form of reports. Thus, since research planning is always involved, the research then monitors, records and collects data, then analyzes the data and ends by reporting the results of the research. The results of the research show that the observation results in cycle 1 obtained a percentage at the first meeting, namely 62% and at the second meeting, the score was 60%. Based on the percentage results, it shows that student activities for cycle 1 actions are classified as sufficient. The results of student observations in cycle 1 at first meeting obtained a score percentage of 62% and at the second meeting the score was 68%. The results of the second cycle student observations obtained a percentage in the first meeting, namely 81% and in the second meeting the score was 91%. Based on these results, it shows that student activities for cycle II actions are classified as very good.